Trustworthiness Measure for e-Service - Chang, Elizabeth; Hussain, Farookh; Dillon, Tharam S. (University of New Brunswick, Canada, 2005)
Traditionally, transactions were carried out face-to-face, now, they are carried out over the Internet. The infrastructure for the above business and information exchange could be client-server, peer-to-peer or mobile network environments, and very often users on the network carry out interactions in one of three forms:Anonymous (No names are identified in the communication)Pseudo-anonymous (Nicknames are used in the communication)Non-anonymous (Real names are used in the communication).Incapability or a fraudulent practice could occur when the seller or business provider or buyer (the agents on the network) does not behave in the manner that is mutually agreed or understood, especially if published terms and conditions exist.This paper evaluates currently existing trustworthiness systems and points out that currently there is no existing standardized measurement system for Quality of Service and outlines the methodology that we have developed for this.